(untitled) (Research, Society and Development, 2021)
Objective: To analyze the sociodemographic, clinical and therapeutic characteristics of people undergoing bowel transit reconstruction. Methodology: this is a retrospective, descriptive-analytical, quantitative study, carried out in a specialized rehabilitation center in a city of São Paulo, with a survey of 134 records of patients who underwent Bowel Transit Reconstruction (BTR), approved by the Ethics Committee in Research (nº 2,831,709). Results and discussion: With the analysis of medical records of the population of patients who underwent BTR 134 (100%), an average age of 57.3 years was obtained, predominantly male 78 (58%), of the attendance by the public health system. health 122 (91%); oncologic diagnosis 63 (47%); urgent surgery 88 (66%); and 92 (69%) people with colostomies. There was a statistically significant correlation between type of ostomy, character of the surgery, surgical technique and the diagnosis of surgical indication, differently from the surgery variables and the time of ostomy. Conclusion: There is a need for prevention and early diagnosis of colorectal cancer, in addition to planning health care for the follow-up of surgical and oncological control, to speed up BTR when possible, in addition to preparing this clientele for changes in after BTR, as well as in the management of the forecast and provision of collection equipment and adjuvants, which requires integration of the actions of the different levels of service of this clientele.